Bilateral vestibular hypofunction: a literature review and a case report - Katarzyna Miśkiewicz-Orczyk; Grażyna Lisowska; Sylwia Szostak-Rogula; Michał Szlęzak (Nofer Institute of Occupational Medicine, 2021)
Bilateral vestibular hypofunction (BVH) is a rare disorder of the peripheral part of the balance organ, which may cause chronic vertigo and oscillopsia accompanying body movements. The chronic and severe nature of the symptoms and difficulties in maintaining balance and performing precise movements may cause the patient's withdrawal from professional activity. A frequently long period from the onset of the symptoms to the diagnosis of BVH, which should be based on the objective examination of the peripheral part of the vestibular organ, drastically reduces the chances of improving the patient's precise movement motility and significantly deteriorates the quality of life. Due to the fact that this disease most often affects professionally active patients in the sixth decade of their life, it can become the cause of a loss of the source of income. The publication presents a case report and examination methods of a patient with BVH caused by the administration of gentamicin in the course of phlegmon of the thumb. The case analysis was performed on the basis of a literature review on the diagnosis and treatment of patients with BVH. Med Pr. 2021;72(2):185-92